Identification and characterization of fungal contamination on spent mushroom substrate - Antong Ibrahim, Nur Natasha (2017)
Fungal contamination on spent mushroom substrate is the main problems faced by the mushroom growers in Malaysia. Among many pest and diseases in oyster mushroom cultivation, the most serious crop losses due to fungal contamination by Trichoderma sp., Aspergillus spp.,Penicillium sp. and Fusarium sp. that lead to green mould infection or other mould contamination. Many researchers have undergone the experiment in order to detect the fungal species that attack on mushroom substrates. The objectives of this experiment are (1) to isolate pure culture of fungal isolation causing fungal contamination on spent mushroom substrate (2) to identify fungal pathogens to species level based on morphology characteristics and Polymerase Chain Reaction (PCR) protocol using ITS1 and ITS4 (3) to construct internal transcribed spacer (ITS) phylogeny of fungal species using Maximum Likelihood method. Fungal strains were isolated from diseased mushroom bags from mushroom houseUniversiti Putra Malaysia. The pure fungi isolated from spent mushroom substrate were identified by in vitro morphological and molecular characteristics. Based on morphological characteristics, Aspergillus oryzae had caused fungal contamination on the mushroom substrate by the formation of ampulliformphialide and green coloured conidia also supported by the result of DNA sequencing and amplification using ITS1 and ITS4. Data obtained also had been analyzed to identify phylogeny of fungal species using Maximum Likelihood method.